2021
DOI: 10.1101/2021.07.29.454368
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A machine-learning approach for detection of local brain networks and marginally weak signals identifies novel AD/MCI differentiating connectomic neuroimaging biomarkers

Abstract: Introduction: A computationally fast machine learning method is introduced for uncovering the whole-brain voxel-level connectomic spectra that differentiates different status of Alzheimer's disease (AD). The method is applied to the Alzheimer's Disease Neuroimaging Initiative (ADNI) Fluorine-fluorodeoxyglucose Positron Emission Tomography (FDG-PET) imaging and clinical data and identified novel AD/MCI differentiating connectomic neuroimaging biomarkers. Methods: A divide-and-conquer algorithm is introduced for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Through a series of work, Li et al [19][20][21][22][23] have shown that in cancer-genomic studies, some genes, even though having weak marginal differential effects (DE), may still exude strong prediction effects on disease outcomes though regulating other strong DE genes. These weak DE genes (or weak genes), together with their coregulated strong genes and the coregulations between them, form predictive gene networks (PDN).…”
Section: Introductionmentioning
confidence: 99%
“…Through a series of work, Li et al [19][20][21][22][23] have shown that in cancer-genomic studies, some genes, even though having weak marginal differential effects (DE), may still exude strong prediction effects on disease outcomes though regulating other strong DE genes. These weak DE genes (or weak genes), together with their coregulated strong genes and the coregulations between them, form predictive gene networks (PDN).…”
Section: Introductionmentioning
confidence: 99%